Pertanggungjawaban Pengelola Tpa Terhadap Pencemaran Udara Yang Berdampak Pada Kesehatan Masyarakat: Studi Di Desa Anjani, Kecamatan Suralaga, Kabupaten Lombok Timur - Gita Alit Srinadi, Ida Ayu; Mustafa Umami, Allan (Faculty of Law, University of Mataram, 2024)
This research aims to analyze the “Responsibility of Landfill Managers for Air Pollution Impacting Public Health: A Study in Anjani Village, Suralaga Subdistrict, East Lombok Regency.